MOTIVASI RUSIA MENERAPKAN KEBIJAKAN CUSTOMS UNION TERHADAP EKSPOR IKAN DARI INDONESIA TAHUN 2013 - Annisa Rahayu Putri; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study is a qualitative research which describes Russia motivation applying temporary restriction of fish products exported from Indonesia to Russia dealing with Customs Union policy on July 1, 2013. The restriction applied was based on the result of joint inspection done by Customs Union and Rosselkhoznadzor Russia to some fish companies in Indonesia which found that the companies did not meet the requirements and standard of Customs Union and Rosselkhoznadzor. From the result of the inspection it was found that some problems on fish productions process and lack of certification and documents.Finally, after more than one year of hard effort an negotiation done with Russia authority, the restriction can be released on September 17, 2014. The most important thing for Customs Union and Rosselkhoznadzor is that for Indonesian fish companies to do some improvements and meet the requirements and standard of export agreed by the two parties, such as healthy and safety control and documents.The data were collected from many sources like books, journals, and websites that can support this research. In this research, the researcher uses merkantilism perspective to describe the Russia motivation on temporary restriction of fish products exported from Indonesia.Keywords: Motivation,Customs Union, Export,Temporary Restriction, Fish Products, Negotiation